Playing the Fool: The Satire of Canadian Cultural Nationalism in Mordecai Richler’s The Incomparable Atuk - Morra, Linda (Studies in Canadian Literature, 2001)
In The Incomparable Atuk, Mordecai Richler is just short of prophetic on the subject of Canadian cultural nationalism. Previous criticism underestimates the sophistication of The Incomparable Atuk's satire and trivializes its serious intent. An examination of Atuk reveals his composite nature as both the Trickster of Native culture and the fool figure of Western imperial culture. By transgressing social and geographical boundaries Atuk as Trickster undermines and reveals the authoritarian forces that have designated a marginal space for him and his people. However, as the fool accountable to his patron, Buck Twentyman, Atuk simultaneously invokes white, Western conventions. Atuk plays upon such stereotypes as Eskimo, Jew, "noble savage," and "lazy Native," finding them useful for public image and commercial enterprising. Richler uses Atuk to critique corruption, hypocrisy, and colonial mindedness. Both Twentyman and Atuk capitalize on the flaws of Canadian citizens, and thus are both representative of imperialists who colonize their subjects for personal worldly success. The serious subtext of The Incomparable Ark suggests that Canadians must move beyond insularity, beyond producing "junk," to creating authentic work.